Traces of Ink Experiences of Philology and Replication - Raggetti, Lucia (Nuncius Series, 2021)
Traces of Ink. Experiences of Philology and Replication is a collection of original papers exploring the textual and material aspects of inks and ink-making in a number of premodern cultures (Babylonia, the Graeco-Roman world, the Syriac milieu and the Arabo-Islamic tradition). The volume proposes a fresh and interdisciplinary approach to the study of technical traditions, in which new results can be achieved thanks to the close collaboration between philologists and scientists. Replication represents a crucial meeting point between these two parties: a properly edited text informs the experts in the laboratory who, in turn, may shed light on many aspects of the text by recreating the material reality behind it. Readership: Historians of premodern science, philologists working on the Graeco-Roman, Syriac, and Arabic tradition, along with chemists and natural scientists, in particular those cooperating with humanists.